PERBAIKAN STASIUN KERJA MENURUNKAN AKTIVITAS LISTRIK OTOT DAN KELUHAN MUSKULOSKELETAL PADA PERAJIN UKIR KAYU DI DESA BATUAN GIANYAR BALI - Putri, Putu Dyah Wulandari; Griadhi, I Putu Adiartha (E-Jurnal Medika Udayana, 2015)
IMPROVEMENT OF WORK STATION REDUCE MUSCLE ELECTRICAL ACTIVITY AND MUSCULOSKELETAL COMPLAINTS AMONG WOOD CRAFTSMEN IN BATUAN VILLAGE GIANYAR BALI The role of humans in the industrialized world as a source of labor is still dominant in the work, especially in the manual activities. Manual work, particularly with regard to the strength and endurance of humans in their worklead to problems namely ergonomic problems, including back pain, neck pain, pain in the wrists, elbows and feet called musculoskeletal disorders. In addition, unergonomicworking conditionsincrease theelectrical activity of musclesthat measured bysurfaceelectromyography. This studyaimed to reducemuscleelectrical activity andmusculoskeletal complaintsthroughimprovement of workstationbased on ergonomic. Treatment by subject design was used in this experimentalstudyamongwoodcraftsmeninBatuanvillage GianyarBaliwith atotal 10 male subjects. Theelectrical activity of muscleswere measured when working in conventional working condition (1 st Period) andwith improved work stations(2 nd Period). While, musculoskeletal complaintswere measuredbefore andafterworkingwitha conventionalworking conditions(1 st Period) and with improved work stations(2 nd Period). Datameasurement resultsbetween the twoperiodswere analyzedwithPaired Samples t TestandWilcoxonSigned RanksTest.Dataresultsshowed thatTrapeziusmuscleelectricalactivitydecreased by17.44% andErector Spinaemuscleelectrical activitydecreased by12.28% afterwork station improvement and the averageof musculoskeletal disordersalso decreased by 8.9as measuredafterworkingin the 1 st Periodand2 nd Period. It was concluded thatimprovement of work stations based onergonomiccan reducemuscleelectrical activityand musculoskeletal complaintsamong woodcraftsmenin Batuanvillage GianyarBali.
Keywords: manual work; ergonomics; muscleelectrical activity; musculoskeletal complaints; surface electromyography